Acute otitis media symptoms and symptom scales in research with Aboriginal and Torres Strait Islander children - Penelope Abbott; Caitlin Frede; Wendy C. Y. Hu; Sanja Lujic; Steven Trankle; Letitia Campbell; Hasantha Gunasekera; Robyn Walsh; Amanda J. Leach; Peter Morris; Kelvin Kong; Jennifer Reath (PLoS ONE, 2023)
Background Aboriginal and Torres Strait Islander children experience a high burden of otitis media. We collected data on symptoms associated with acute otitis media (AOM) in a clinical trial involving children receiving primary care at urban Aboriginal Medical Services. Two scales were employed to monitor symptoms over time: the AOM-Severity of Symptoms scale (AOM-SOS) and the AOM-Faces Scale (AOM-FS). This study took place at a mid-point of the un-blinded trial. Methods We examined symptoms at enrolment and day 7, and compared the scales for trends, and bivariate correlation (Spearman’s rho) over 14 days. Responsiveness of the scales to clinical change was determined by Friedman’s test of trend in two subgroups stratified by day 7 AOM status. We interviewed parents/carers and research officers regarding their experience of the scales and analysed data thematically. Results Data derived from 224 children (18 months to 16 years; median 3.6 years). Common symptoms associated with AOM at baseline were runny nose (40%), cough (38%) and irritability (36%). More than one third had no or minimal symptoms at baseline according to AOM-SOS (1-2/10) and AOM-FS scores (1-2/7). The scales performed similarly, and were moderately correlated, at all study points. Although scores decreased from day 0 to 14, trends and mean scores were the same whether AOM was persistent or resolved at day 7. Users preferred the simplicity of the AOM-FS but encountered challenges when interpreting it. Conclusion We found minimally symptomatic AOM was common among Aboriginal and Torres Strait Islander children in urban settings. The AOM-SOS and AOM-FS functioned similarly. However, it is likely the scales measured concurrent symptoms related to upper respiratory tract infections, given they did not differentiate children with persistent or resolved AOM based on stringent diagnostic criteria. This appears to limit the research and clinical value of the scales in monitoring AOM treatment among Aboriginal and Torres Strait Islander children.